Sekolah Muhammadiyah Zaman Colonial Belanda di Kota Bengkulu - Shinta Lestari Oktarini (LPPM IAIN Sorong, 2022)
Abstract Past Islamic education needs special attention, such as Islamic education in the Dutch colonial era in Bengkulu. Where now has taken an important role for the course of Islamic education in Bengkulu. The history of Islamic education in Bengkulu is inseparable from the role of Islamic organizations. One of the Islamic organizations that took the role was Muhammadiyah. Muhammadiyah contributed greatly to the running of Islamic schools iin Bengkulu. Andd the existence oof the Dutch colonialists became one of the difficulties in building Muhammadiyah schools in Bengkulu. The purposee of this study is to describe the history and development off Muhammadiyah schools iin Bengkulu since tthe Dutch colonial period. This research wass conducted by qualitative method with literature sstudy. The resultss of this study are first, Muhammadiyah was present iin Bengkulu around 1926 which was pioneered by Bustanul Icshan. Second, Muhammadiyah during the Dutch period was able to create various Muhammadiyah-level schools. Third, Muhammadiyah schools in Bengkulu can still run but under the supervision of the Dutch colonial. Keywords: Muhammadiyah, Islamic Education, Dutch Colonial Periode Abstrak Pendidikan islam masa lalu perlu mendapat perhatian khusus, seperti pendidikan islam di zaman penjajahan Belanda di Bengkulu. Dimana sekarang telah mengambil peranan penting bagi jalanya pendidikan islam di Bengkulu. Perjalanan sejarah pendidikan islam di Bengkulu tidak terlepas dari peran organisasi islam. Salah satu organisasi Islam yang mengambil peran adalah muhammadiyah. Muhammadiyah berjasa besar bagi jalannya sekolah islam di Bengkulu. Dan adanya penjajah belanda menjadi salah kesulitan tersendiri dalam membangun sekolah muhammadiyahh di Bengkulu. Tujuan dari penelitian iini adalah mendeskripsikann sejarah dan perkembangan sekolah Muhammadiyah dii Bengkulu sejakk masa kolonial Belanda. Penelitian ini dilakukan dengan metode kualitatif denganm studi kepustakaan. Hasill dari penelitian ini adalah pertama, Muhammadiyah telah hadir di Bengkulu sekitar tahun 1926 yang dipelopori oleh Bustanul Icshan. Kedua, Muhammadiyah pada masa belanda sudah mampu menciptakan berbagai sekolah bertaraf muhammadiyah. Ketiga, Sekolah muhammadiyah di Bengkulu tetap bisa berjalan tetapi dalam pengawasan kolonial belanda. Kata Kunci: Muhammadiyah, Pendidikan Islam, Masa Penjajahan Belanda